2022
DOI: 10.1093/jbcr/irac099
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Implementing a Beta-lactam Therapeutic Drug Monitoring Service in a Burn Intensive Care Unit: A Retrospective Chart Review

Abstract: Thermal injuries alter pharmacokinetics, complicating the prediction of standard antibiotic dose effectiveness. Therapeutic drug monitoring has been proposed to prevent subtherapeutic dosing of antibiotic therapy, but remains scarcely studied in the burn patient population. A retrospective chart review of burn patients receiving beta-lactam therapeutic drug monitoring from 2016 to 2019 was conducted. Adult patients with thermal injury receiving cefepime, piperacillin/tazobactam, or meropenem for ≥48 hours were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Moreover, they estimated that different regimens (1 g every 8 h, 2 g every 12 h or 2 g every 8 h, administered over 30 min) were sufficient to achieve a target of 60% T > MIC with MIC values ≤ 8 mL/L. In addition, Alshaer et al [22] recently performed a before/after study investigating the implementation of TDM in a burn unit. They administered 6 g of cefepime (mean values not specified at patient level) in 42 infectious episodes and found an overall PTA ranging from 60% to 100%, according to different targets.…”
Section: Cefepimementioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, they estimated that different regimens (1 g every 8 h, 2 g every 12 h or 2 g every 8 h, administered over 30 min) were sufficient to achieve a target of 60% T > MIC with MIC values ≤ 8 mL/L. In addition, Alshaer et al [22] recently performed a before/after study investigating the implementation of TDM in a burn unit. They administered 6 g of cefepime (mean values not specified at patient level) in 42 infectious episodes and found an overall PTA ranging from 60% to 100%, according to different targets.…”
Section: Cefepimementioning
confidence: 99%
“…Four papers [14,15,22,41] reported monocentric experiences of the implementation of TDM in guiding antibiotic treatment in burn patients, including piperacillin or piperacilintazobactam. Patel et al [41] reported using TDM in a sample of 50 burn patients, which included 6 patients treated with 4.5 g piperacillin-tazobactam every 6 h. Given an MIC of 2 mg/L, they reported attaining a 100% fT > 4 × MIC target in 2/6 patients (34%).…”
Section: Piperacillin-tazobactammentioning
confidence: 99%
See 3 more Smart Citations